2012
DOI: 10.1093/eurheartj/ehs232
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 2, randomized, partially blinded, active-controlled study assessing the efficacy and safety of variable anticoagulation reversal using the REG1 system in patients with acute coronary syndromes: results of the RADAR trial

Abstract: At least 50% reversal is required to allow safe sheath removal after cardiac catheterization. REG1 appears a safe strategy to anticoagulate ACS patients managed invasively and warrants further investigation in adequately powered clinical trials of patients who require short-term high-intensity anticoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 29 publications
1
62
0
2
Order By: Relevance
“…Частота тром-ботических осложнений в течение 30 дней в группе RB006/RB007 (все подгруппы) была не-сколько ниже, чем в группе гепарина, однако эти отличия не достигали достоверного уров-ня -3,0% и 5,1% соответственно (p = 0,1). К важным наблюдениям этого исследования сле-дует отнести регистрацию 3 случаев развития аллергических осложнений среди больных, получавших RB006 [21].…”
Section: новые направления в антитромботической терапииunclassified
“…Частота тром-ботических осложнений в течение 30 дней в группе RB006/RB007 (все подгруппы) была не-сколько ниже, чем в группе гепарина, однако эти отличия не достигали достоверного уров-ня -3,0% и 5,1% соответственно (p = 0,1). К важным наблюдениям этого исследования сле-дует отнести регистрацию 3 случаев развития аллергических осложнений среди больных, получавших RB006 [21].…”
Section: новые направления в антитромботической терапииunclassified
“…This dual system allows precise control of the pharmaceutical effects on blood clotting and was designed for the prevention of bleeding within surgical interventions. Early clinical evaluations showed promising results for use as anticoagulation agent during interventions for acute coronary syndrome [66]. A comprehensive Phase III trial, however, had to be terminated in late 2014 because of occurrences of severe anaphylactic reactions.…”
Section: Aptamersmentioning
confidence: 99%
“…A comprehensive Phase III trial, however, had to be terminated in late 2014 because of occurrences of severe anaphylactic reactions. Although a clear proof is lack- 10.4155/fmc.15.94 www.future-science.com future science group Therapeutic oligonucleotides with polyethylene glycol modifications Review ing, it can be speculated that a PEG-reactive antibody mediated mechanism is responsible for the allergic reactions [66]. As stated before, a considerable share of individuals carry antiPEG antibodies, possibly caused by the increasing use of PEG not only in drugs, but also in cosmetics and other consumer products.…”
Section: Aptamersmentioning
confidence: 99%
“…Although this approach does not necessarily lead to a better risk/benefit ratio, its anticoagulant activity can be rapidly and easily controlled by developing a complementary, anti-sense oligonucleotide to neutralize the aptamer. On a clinical basis, this approach has been most fully studied with the factor IX aptamer known as the REG 1 or 2 Anticoagulation System (REG2; Regado Biosciences, Inc., Basking Ridge, NJ) [13,14]. Studies have shown that factor IXa inhibition provides a clinically useful antithrombotic signal [15].…”
Section: Improving the Benefit/risk Of Anticoagulant Drugsmentioning
confidence: 99%
“…In the REG system, pegnivacogin, a nuclease-stabilized RNA aptamer, when given subcutaneously, binds to and inhibits factor IXa with high affinity and specificity and is reversed by its complementary oligonucleotide, anivamersen. Initial studies with intravenous pegnivacogin (REG 1) showed its ability to anticoagulate patients and be reversed by anivamersen in a Phase 2 trial in patients with acute coronary syndromes [13]. A recent first-inhuman study of REG 2 (subcutaneous pegnivacogin) demonstrated its ability to neutralize thrombin generation in a dose response manner with reversal by anivamersen without evidence of rebound effect [14].…”
Section: Improving the Benefit/risk Of Anticoagulant Drugsmentioning
confidence: 99%